An Update of Wallace's Zoogeographic Regions of the World - Holt, Ben G.; Lessard, Jean-Philippe; Borregaard, Michael K.; Fritz, Susanne A.; Araújo, Miguel B.; Dimitrov, Dimitar; Fabre, Pierre-Henri; Graham, Catherine H.; Graves, Gary R.; Jønsson, Knud A.; Nogués-Bravo, David; Wang, Zhiheng; et al. (Science (American Association for the Advancement of Science), 2013)
Modern attempts to produce biogeographic maps focus on the distribution of species, and the maps are typically drawn without phylogenetic considerations. Here, we generate a global map of zoogeographic regions by combining data on the distributions and phylogenetic relationships of 21,037 species of amphibians, birds, and mammals. We identify 20 distinct zoogeographic regions, which are grouped into 11 larger realms. We document the lack of support for several regions previously defined based on distributional data and show that spatial turnover in the phylogenetic composition of vertebrate assemblages is higher in the Southern than in the Northern Hemisphere. We further show that the integration of phylogenetic information provides valuable insight on historical relationships among regions, permitting the identification of evolutionarily unique regions of the world.